The Study of Two Affiliated Modern Stores as an Emphasis and Brand Differentiation - dedi himawan (INJECT (Interdisciplinary Journal of Communication), 2022)
It is undeniable that nowadays minimarkets are getting more numerous, Alfamidi and Alfamart seem to have the same thing, but in fact the two minimarkets have differences in their marketing strategies. The purpose of this study is to determine the strategy of developing modern retail Alfamidi as a Compact Supermarket through the promotion of the logo, tagline, mascot, for the purpose of captivating consumers' hearts and becoming number one in the minds of the people (Top of Mind). This study uses a qualitative approach with descriptive and exploratory approaches, namely collecting data based on these factors to find out their roles. The results showed that in terms of product marketing strategies, Alfamidi added a variety of products that are more segmented and varied than other competing retailers. In terms of branding, Alfamidi uses the tagline "Satisfied Shopping at Economical Prices, with a mascot that was created by giving a special touch so that it sticks firmly in the minds of the people. This is part of a differentiation strategy, or concrete steps in communicating the Alfamidi brand that is unique and different from other retail trademarks. However, the facts in the field show that Alfamidi's Product Marketing Strategy and Branding Communication Strategy, even though they have been able to present product uniqueness and customer enjoyment, have triggered awareness of commitment and love for the brand, but have not played a significant role in realizing customer loyalty to the brand (brand loyalty).Keywords: Differentiation Strategy, Branding, Brand Awareness